2022
DOI: 10.1364/boe.449046
|View full text |Cite|
|
Sign up to set email alerts
|

Complete head cerebral sensitivity mapping for diffuse correlation spectroscopy using subject-specific magnetic resonance imaging models

Abstract: We characterize cerebral sensitivity across the entire adult human head for diffuse correlation spectroscopy, an optical technique increasingly used for bedside cerebral perfusion monitoring. Sixteen subject-specific magnetic resonance imaging-derived head models were used to identify high sensitivity regions by running Monte Carlo light propagation simulations at over eight hundred uniformly distributed locations on the head. Significant spatial variations in cerebral sensitivity, consistent across subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 60 publications
4
32
0
Order By: Relevance
“…During pressure modulation, the reduction was only 23 ± 4% at the 1.5 cm separation late gate compared to 57 ± 6% at the short (0.5 cm) separation, indicating a substantial degree of CBF sensitivity, thus giving confidence that the signals measured at late gates are derived from cerebral signals. We also note that our results matched the recent simulation study ( Wu et al, 2022 ) that found lower extracerebral thickness at the lateral side of the forehead results in higher sensitivity with respect to more medial locations. This is in good agreement with our pressure modulation task results where we found a 6.7 ± 2.8% greater reduction with pressure modulation in the medial locations compared to the lateral locations indicating somewhat higher extracerebral contribution.…”
Section: Discussionsupporting
confidence: 91%
“…During pressure modulation, the reduction was only 23 ± 4% at the 1.5 cm separation late gate compared to 57 ± 6% at the short (0.5 cm) separation, indicating a substantial degree of CBF sensitivity, thus giving confidence that the signals measured at late gates are derived from cerebral signals. We also note that our results matched the recent simulation study ( Wu et al, 2022 ) that found lower extracerebral thickness at the lateral side of the forehead results in higher sensitivity with respect to more medial locations. This is in good agreement with our pressure modulation task results where we found a 6.7 ± 2.8% greater reduction with pressure modulation in the medial locations compared to the lateral locations indicating somewhat higher extracerebral contribution.…”
Section: Discussionsupporting
confidence: 91%
“…To illustrate, Fig. 2(a) shows the distribution of the straight line distance between the scalp surface and gray matter in different areas of the head, derived from a set of segmented MRI scans collected as part of a previous study (16 subjects, average age 29, range 25 to 41), 35 and subplots shown in Figs. 2(b) and 2(c) show the fractional recovery of a true blood flow change in the scalp and brain tissue, respectively, using simulation data from the same study 35 for the 25-mm source-detector separation used in the majority of published DCS investigations.…”
Section: Benefits and Challengesmentioning
confidence: 99%
“…2(a) shows the distribution of the straight line distance between the scalp surface and gray matter in different areas of the head, derived from a set of segmented MRI scans collected as part of a previous study (16 subjects, average age 29, range 25 to 41), 35 and subplots shown in Figs. 2(b) and 2(c) show the fractional recovery of a true blood flow change in the scalp and brain tissue, respectively, using simulation data from the same study 35 for the 25-mm source-detector separation used in the majority of published DCS investigations. As can be seen in these graphs, not only is the average brain sensitivity fairly low (on the order of 20% for typical scalp to brain distances in the frontal region for example), but the measurement has higher sensitivity to scalp than to brain blood flow.…”
Section: Benefits and Challengesmentioning
confidence: 99%
See 2 more Smart Citations